Development of the socio-cultural competence of student teachers on the basis of the findings on the topic “German traces in Ukraine” (Educational Dimension, 2020)
The article is devoted to the formation of socio-cultural competence of students, which is one of the components of linguistic-socio-cultural competence and is an integral part of foreign language communicative competence. There are considered different approaches to the formation of socio-cultural competence (cognitive, communicative, intercultural) and the possibility of developing materials on the basis of the topic “German traces in Ukraine”. Within the article exercises developed by using mobile applications and WEB 2.0 tools, the material for which were lexical units and texts on the topic, may be found. In the conclusion it is mentioned that the topic “German traces in Ukraine” has great potential for the formation of socio-cultural competence of students and contributes the motivation to learn German.